2008
DOI: 10.1186/1746-6148-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Salmonella enterica serotype Typhimurium isolates from wild birds in northern England from 2005 – 2006

Abstract: Background: Several studies have shown that a number of serovars of Salmonella enterica may be isolated from wild birds, and it has been suggested that wild birds may play a role in the epidemiology of human and livestock salmonellosis. However, little is known about the relationship between wild bird S. enterica strains and human-and livestock-associated strains in the United Kingdom. Given the zoonotic potential of salmonellosis, the main aim of this study was to investigate the molecular epidemiology of S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 35 publications
8
115
0
6
Order By: Relevance
“…Although the direct association of virulence and resistance is not determined in this study, much epidemiological data support the idea that, in some cases, antibiotic-resistant organisms may show a decrease in pathogenicity [24][25][26]. The opposite situation might also occur [27][28][29].Two of the seven genes, sopB and pipD associated with resistance in our study, were also associated with enteritis or epidemic disease in both children and animals [11,15,16]. This result shows that our isolates could also exhibit such epidemic potential since these virulence genes were detected in almost all diarrhoeic children.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Although the direct association of virulence and resistance is not determined in this study, much epidemiological data support the idea that, in some cases, antibiotic-resistant organisms may show a decrease in pathogenicity [24][25][26]. The opposite situation might also occur [27][28][29].Two of the seven genes, sopB and pipD associated with resistance in our study, were also associated with enteritis or epidemic disease in both children and animals [11,15,16]. This result shows that our isolates could also exhibit such epidemic potential since these virulence genes were detected in almost all diarrhoeic children.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that the sopE gene was present in strains of S. Typhimurium associated with epidemic disease in both humans and animals [16] and therefore the sopE gene if expressed may be implicated in diseases in both children and animals in The Gambia. In addition, the sopB and pipD genes, which are associated with enteritis in birds [11,15], were present in 94.1% and 92.4% of all serovars tested, respectively, including those isolated from diarrhoeic children. Furthermore, the invA gene was detected in 99.5% of Salmonella serovars in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Working DNA solutions were prepared by diluting stock solutions to 5 ng/l. Primers for each gene were designed using the primer design feature in GenBank or were obtained from Hughes et al (46). Primers were obtained from GeneWorks (Adelaide, South Australia) ( Table 4 The product sizes for each of the genes were relatively similar.…”
Section: Selection Of Farmsmentioning
confidence: 99%